Retention in MOOCS: some key factors - Andrés Chiappe; Blanca Diana Lorena Castillo (Ensaio, 2021)
The dropping out of students in the Massive Open Online Courses (Mooc) has been the subject of debate and concern on the part of educational researchers and practitioners during the last decade. Considering its growth as an educational trend and the emerging research generated on this topic, a systematic review of literature on 131 studies was conducted about attrition in both cMooc and xMoocs. The results highlight the role of collaboration, the sense of community, the need for certification and standardization as the main factors that affect attrition in Moocs.